2009
DOI: 10.1016/j.immuni.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mapping of Thymic Stromal Microenvironments Reveals Unique Features Influencing T Lymphoid Differentiation

Abstract: Summary Interaction of hematopoietic progenitors with the thymic stromal microenvironment induces them to proliferate, adopt the T cell fate, and asymmetrically diverge into multiple T lineages. Progenitors at various developmental stages are stratified among different regions of the thymus, implying that the corresponding microenvironments differ from one another, and provide unique sets of signals to progenitors migrating between them. The nature of these differences remains undefined. Here we use novel phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 60 publications
4
89
1
Order By: Relevance
“…Several lines of evidence indicate that these cytokines are available to developing γδ T cells in the thymus. Previous work by Petrie and colleagues showed that IL-1β and IL-23 are expressed by mTECs at comparable levels to IL-7 42 . Moreover, specific subsets of thymic γδ T cells and a population of CD4 + T cells express high levels of IL-21R, during the appropriate ontological window of time to affect γδ17 development (www.immgen.org) 43 , plus a subset of IL-21 expressing thymocytes was recently reported 44 .…”
Section: Resultsmentioning
confidence: 94%
“…Several lines of evidence indicate that these cytokines are available to developing γδ T cells in the thymus. Previous work by Petrie and colleagues showed that IL-1β and IL-23 are expressed by mTECs at comparable levels to IL-7 42 . Moreover, specific subsets of thymic γδ T cells and a population of CD4 + T cells express high levels of IL-21R, during the appropriate ontological window of time to affect γδ17 development (www.immgen.org) 43 , plus a subset of IL-21 expressing thymocytes was recently reported 44 .…”
Section: Resultsmentioning
confidence: 94%
“…Age-related thymic degeneration is a significant impediment in cancer patients undergoing HSCT because the conditioning regimens damage already reduced stromal cell niches in recipient thymi (41)(42)(43)(44). In elderly patients, the impaired T-cell reconstitution due to thymic damage after HSCT results in prolonged posttransplant T-cell deficiency and significant mortality and morbidity (43).…”
Section: R F G F O H T O L K -B 2 R F G F 3 R F G F 4 R F G F 2 F G Fmentioning
confidence: 99%
“…Recently, a similar approach was used to analyze the gene expression of the thymic stromal microenvironments [45]. Data sets obtained from dissected FDC networks were compared with those of sorted B cells.…”
Section: Microarray Analysismentioning
confidence: 99%